Differences in plasmatic butyrylcholinesterases (BChE) values between Pacific and Caribbean populations of terciopelo (Bothrops asper) in Costa Rica - Arguedas Porras, Randall (2019)
The terciopelo (Bothrops asper) inhabits human-modified environments such as agricultural areas, becoming more prone to be exposed to organophosphate insecticides. These chemicals can inhibit plasmatic butyrylcholinesterases (BChE) activity in B. asper. Caribbean and Pacific populations of B. asper belong to two divergent lineages that exhibit robust genetic partitioning; however, differences across versants in biochemistry and hematology have not yet been examined, especially in BChE variations. This study aims to evaluate the differences of BChE plasmatic values, hematology parameters, and some biochemical analytes as biomarkers in the presence of organophosphates between the Pacific and Caribbean population of B. asper in Costa Rica. A total of 89 snakes (41 Pacific and 48 Caribbean) were used, and hematology parameter, albumin, aspartate aminotransferase (AST), total protein and BChEs were evaluated. Differences in hemoglobin content, thrombocytes, white cell count, AST, and BChE values were found between both versants. Intrinsic genetic factors might influence the variation found in BChE and AST values in the snakes sampled from both versants; moreover, understanding this variation in BChE and AST values across the B. asper's distribution can be useful in future ecotoxicology, biomonitoring, genetic and other clinical/health studies.